The Role of Democracy Volunteers in Increasing Voter Participation in the Year of 2019 General Election at Samosir Regency - Bonita Carolina Iriany Sitompul; R. Hamdani Harahap; Heri Kusmanto (PERSPEKTIF, 2023)
The purpose of this study was to find out the role of democracy volunteers in increasing participation in the 2019 general election in Samosir Regency. Apart from that, to find out how democracy volunteers socialize more massively and intensively to voters is also needed to reduce the number of invalid votes or invalid votes in elections. This research method is descriptive qualitative, namely by presenting the facts found comprehensively through in-depth analysis. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. The research results obtained showed that the Democracy Volunteers for the Samosir Regency had carried out their role in the 2019 Election, namely conducting outreach and voter education, including by providing information about the implementation of elections and inviting people to become smart voters. The pattern of socialization carried out by the Democracy Volunteers is classified as different, this is based on the segmentation of community groups. In addition, there are several Democratic Volunteer Bases that have similarities or similarities in carrying out socialization patterns